Orientasi dan Perkembangan Regulasi Perbankan Syariah - Moh Ulumuddin (AT-Tahdzib: Jurnal Studi Islam dan Muamalah, 2018)
Banking regulation in command (UU No 14 years 1967 on banking points up to the last regulation of UU No 21 year 2011 on OJK, so that there is a clear description of the history of regulatory developments Sharia banking. The presence of Sharia banks in the midst of conventional banking is at least two main reasons concerning the background of the establishment of Sharia banks, namely: first, from the legal aspect, the view that the interest in the conventional bank The law is unlawful because it belongs to the category of Riba forbidden in religion, not only on the religion of Islam but also by other religious religions; Secondly, from the economic aspect, the surrender of business risk to one party is judged to violate the norms of justice and can cause selfishness.